2005
DOI: 10.1079/phn2005741
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic index, glycaemic load and risk of endometrial cancer: a prospective cohort study

Abstract: Objective: High-glycaemic-load diets may increase endometrial cancer risk by increasing circulating insulin levels and, as a consequence, circulating oestrogen levels. Given the paucity of epidemiological data regarding the relationship between dietary glycaemic index and glycaemic load and endometrial cancer risk, we sought to examine these associations using data from a prospective cohort study. Design, setting and subjects: We examined the association between dietary glycaemic load and endometrial cancer ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 34 publications
3
53
2
Order By: Relevance
“…Risk factors for endometrial cancer are relatively common and include conditions such as obesity, unfavorable glycemic index, diabetes, hypertension and unovulation [18][19][20][21][22]. Although only a small percentage of those women will develop endometrial cancer, the prevalence of risk factors and symptoms such as irregular uterine bleeding and the greater awareness for the risk factors have created a demand by women and caregivers for screening and early detection of endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for endometrial cancer are relatively common and include conditions such as obesity, unfavorable glycemic index, diabetes, hypertension and unovulation [18][19][20][21][22]. Although only a small percentage of those women will develop endometrial cancer, the prevalence of risk factors and symptoms such as irregular uterine bleeding and the greater awareness for the risk factors have created a demand by women and caregivers for screening and early detection of endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Five articles that were identified investigated endometrial cancer (Folsom et al, 2003;Augustin et al, 2003a;Silvera et al, 2005;Larsson et al, 2007;Cust et al, 2007a) and two that investigated ovarian cancer (Augustin et al, 2003b;Silvera et al, 2007); the characteristics of these studies are described in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that some individual studies had a relatively narrow range of GI and GL intakes, which could explain the lack of statistically significant results observed in these studies. In the cohort studies, comparing the highest versus the lowest category of GL intake corresponded to an approximate difference of 50 GL units (Folsom et al, 2003;Silvera et al, 2005Silvera et al, , 2007Cust et al, 2007a;Larsson et al, 2007), whereas in the case -control studies this observed difference was approximately 100 units (Augustin et al, 2003a, b). This could partly explain the stronger association observed in the meta-analysis of endometrial cancer risk and GL when the case -control study was included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Body mass index and duration of hormone replacement use showed dose -response relationships with endometrial cancer risk, and parity and duration of oral contraceptive use were inversely associated with risk (data not shown; see Silvera et al, 2005: Table 1). Cases and non-cases were similar in terms of age at first live birth, smoking status (as well as intensity and duration of smoking), and alcohol consumption.…”
Section: Resultsmentioning
confidence: 99%